The Influence of the Problem-Based Contextual Teaching and Learning (CTL) Method on the PAK Learning Outcomes of Class VIII Students - Olivtia Kesia Pebriany; Prasetiawati Prasetiawati; Urbanus Urbanus (EDUJAVARE: International Journal of Educational Research, 2026)
Christian Religious Education (CRE) has an important role in shaping students’ moral character, spiritual awareness, and value-based decision-making in school life. This study aimed to determine the effect of the Problem-Based Contextual Teaching and Learning (CTL) method on the learning outcomes of Christian Religious Education (CRE) and to examine the differences in learning outcomes between students taught using the Problem-Based CTL method and those taught using the conventional lecture method among eighth-grade students at SMP Kristen Palangka Raya. This research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The sample consisted of 30 students, divided equally into an experimental class and a control class. Data were collected through observation, documentation, pre-tests, and post-tests, and were analyzed using descriptive statistics, normality and homogeneity tests, and the Independent Sample *t*-Test with the assistance of SPSS version 26. The findings revealed that the experimental class achieved a higher mean post-test score (83.13) than the control class (69.80). The Independent Sample *t*-Test produced a significance value of 0.000 (<0.05), indicating that the Problem-Based CTL method had a statistically significant positive effect on students' Christian Religious Education learning outcomes and that students taught using the Problem-Based CTL method performed significantly better than those taught through the lecture method. The results indicate that contextual and problem-based learning promotes active participation, critical thinking, meaningful learning, and the ability to connect biblical concepts with real-life situations, thereby improving students' cognitive achievement.